A new concept for tuning design weights in survey sampling : jackknifing in theory and practice /: jackknifing in theory and practice. (2015) - Singh, Sarjinder, 1963-; Sedory, Stephen; Rueda, Maria; Arcos, Antonio; Arnab, Raghunath
No abstract available